2020
DOI: 10.1101/2020.10.28.358572
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emergent collective organization of bone cells in complex curvature fields

Abstract: Individual cells and multicellular systems have been shown to respond to cell-scale curvatures in their environments, guiding migration, orientation, and tissue formation. However, it remains unclear how cells collectively explore and pattern complex landscapes with curvature gradients across the Euclidean and non-Euclidean spectra, partly owing to fabrication limitations and the lack of formal geometric considerations. Here, we show that micro-engineered substrates with controlled curvature variations induce … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
4
1
Order By: Relevance
“…We observed that devices with microgrooved surfaces had improved cellular attachment over devices with smoothed surfaces, thus we used microgrooved devices for all SPA conditioning studies. While previous studies have shown that similar microscale topologies can affect cellular morphology and alignment [41,42], we observed no significant cell alignment in static culture (SC) replicates due to the microgrooves (figures S2(B) and (C)). Future investigations into how cells respond to competing mechanobiological stimuli would aid in decision-making when choosing the most effective methods for guiding tissue maturation.…”
Section: Cytoskeletal Orientation and Distributioncontrasting
confidence: 81%
“…We observed that devices with microgrooved surfaces had improved cellular attachment over devices with smoothed surfaces, thus we used microgrooved devices for all SPA conditioning studies. While previous studies have shown that similar microscale topologies can affect cellular morphology and alignment [41,42], we observed no significant cell alignment in static culture (SC) replicates due to the microgrooves (figures S2(B) and (C)). Future investigations into how cells respond to competing mechanobiological stimuli would aid in decision-making when choosing the most effective methods for guiding tissue maturation.…”
Section: Cytoskeletal Orientation and Distributioncontrasting
confidence: 81%
“…[156] On 3D sinusoid landscapes, individual cells position themselves in concave regions [4b] but collections of cells coordinate to reach favorable tensional states that allow them to colonize other regions. [157] In concavities, the oriented tension accumulated in the multicellular system often results in tissue detachment. [158] Similarly, epithelial cells grown on flat fibronectincoated substrates with circular nonadhesive islands of various sizes were also observed to spontaneously depart from the surface and form domes of different radii of curvature.…”
Section: Coordination In Multicell Systemsmentioning
confidence: 99%
“…The additively manufactured BSR molds resulted in microscale 3D printing layer lines across the BSR and its recesses and imaged ROIs. Previous studies have shown that similar microscale topological features can affect cellular morphology and alignment [46, 47]. However, no significant cell alignment due to these layer lines was observed for static culture (SC) replicates.…”
Section: Resultsmentioning
confidence: 99%